Nutritional composition, toxicity, and the effects of Parkia biglobosa on the metabolic, somatic and oxidative parameters related to liver and kidney function of obese rats - Mirela Gouveia-Nhanca; Maria Luiza Rolim Bezerra; Yuri Mangueira do Nascimento; Evandro Ferreira da Silva; Josean Fechine Tavares; Gonçalo Mendes da Conceição; Rubens Teixeira de Queiroz; Luis António Tavares; Adriano Francisco Alves; Jailane de Souza Aquino (Journal of Functional Foods)
Background: The pathophysiology of obesity is associated with somatic, metabolic and oxidative changes which can also compromise renal and hepatic function. Treatment of this condition involves dietary intervention, including incorporating foods rich in bioactive compounds such as Parkia biglobosa. This legume is rich in fibres and phenolic compounds such as 3,4-dihydroxybenzoic acid, catechin, and myricetin that can play a significant role in the adjuvant treatment of obesity. Thus, we evaluated the nutritional composition, toxicity, and the effects of Parkia biglobosa on metabolic, somatic and oxidative parameters, as well as the liver and kidney function of obese rats. Methods: Parkia biglobosa pulp was initially characterised and evaluated for its toxicity. Then, male Wistar rats were randomised into groups: healthy (HG); obese (OG); healthy (HPB) and obese (OPB) both treated with Parkia biglobosa (400 mg/kg). Somatic and biochemical parameters; triglyceride, cholesterol and total fat in faeces and liver; oxidative and histological parameters in the liver and kidney were all analysed. Results: Parkia biglobosa intake reduced the adiposity index; improved glucose tolerance, insulin resistance, leptinemia and lipid metabolism parameters, which impacted the minimization of hepatic steatosis and improved oxidative parameters in the kidney and liver in obese rats (OPB). These findings are related to the nutritional composition of this legume, such as the relationship between insoluble and soluble fibres, as well as the phenolic and mineral profile. Conclusion: The set of results showed that Parkia biglobosa had an anti-adiposity effect, improved biochemical including hormonal parameters and reversed the changes in hepatic and renal markers in obesity-induced rats.